2022
DOI: 10.1111/ijcs.12853
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of brand attachment: A literature review and research agenda

Abstract: Consumers develop powerful connections with brands and they feel a strong bond or attachment to favourite brands that can lead to re‐purchase behaviour, reduced price sensitivity and increased customer loyalty. Gaining greater in‐depth knowledge of brand attachment offers a powerful means of understanding and facilitates modelling the mechanisms for achieving greater profitability and increased revenue for firms. The purpose of this paper is first to map the antecedents, mediators and consequences of brand att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 99 publications
1
16
0
2
Order By: Relevance
“…When considering consumers' sensitivity to breaching the brand-consumer relationship contract, brand misconducting behaviours may result in brand transgression. This would cause negative consumer behaviour (Bechwati & Morrin, 2003;Sierra et al, 2010;Sayin & Gürhan-Canlı, 2015;Khamitov et al, 2020;Hemsley-Brown, 2022). We support this assumption in this study because the severity of brand transgressions increases consumers' privacy concerns and, as a result, lowers their trust beliefs.…”
Section: Theoretical Implicationssupporting
confidence: 66%
“…When considering consumers' sensitivity to breaching the brand-consumer relationship contract, brand misconducting behaviours may result in brand transgression. This would cause negative consumer behaviour (Bechwati & Morrin, 2003;Sierra et al, 2010;Sayin & Gürhan-Canlı, 2015;Khamitov et al, 2020;Hemsley-Brown, 2022). We support this assumption in this study because the severity of brand transgressions increases consumers' privacy concerns and, as a result, lowers their trust beliefs.…”
Section: Theoretical Implicationssupporting
confidence: 66%
“…The researchers believe that consumers' willingness to pay a premium is influenced by their attachment to the brand. Consumers who love a brand will continue to buy them even if the price rises (Hemsley-Brown, 2022). They tend to bond strongly with the brands they patronize, making them less sensitive to price changes (Wallace et al, 2022).…”
Section: 4mentioning
confidence: 99%
“…These studies revealed that consumers' judgments significantly shape emotional brand connections. Moreover, the impact of brand feelings on brand resonance has been examined through brand attachment (Hemsley- Brown, 2022). Research has also explored brand feeling's mediation in various contexts including fast-food (Yang and Choi, 2022) and Internet services (Durmaz, 2022).…”
Section: Validationmentioning
confidence: 99%